Health Education, Free Medical Treatment, And Social Service For The Community Of Malingping, Lebak, Banten - Fitriyati Irviana (Abdimas Paspama, 2025)
This community service program aimed to improve public health awareness and access to medical services in Malingping District, Lebak, Banten—an area facing significant barriers to healthcare due to its remote location and limited infrastructure. The program included health education, free medical treatment, and social outreach activities. Educational sessions raised awareness about healthy living, hygiene, and disease prevention, while medical services offered free consultations, blood pressure and glucose screenings, and basic medication. Additionally, the distribution of food packages and hygiene kits provided immediate relief to underprivileged families. The program successfully served over 500 residents and engaged local stakeholders and health professionals. The outcomes demonstrated increased health knowledge, early detection of chronic conditions, and strengthened community resilience. This initiative also served as a field-learning opportunity for students and promoted collaboration between academic institutions and local communities. The integrated approach proved effective in addressing both short- and long-term health challenges in underserved areas.